Fitness and mating compatibility of chrysodeixis includens (W.) (lepidoptera: Noctuidae) populations collected in different provinces and crops in argentina - Dami, Luciana Cecilia (2021)
Chrysodeixis includens, is an important Plusiinae pest that feeds on soybean, beans, and cotton. This species has a genetic structure determined by molecular markers in populations collected in soybean crops in Brazil and has developed resistance to insecticides. This had led to an increased interest in the genetic diversity of its populations in Argentina. This study aimed to characterize the fitness parameters and mating compatibility of geographically distant C. includens populations and on different host plants in Argentina. Intra-and inter-population crosses revealed that C. includens populations from Tucumán and Santiago del Estero provinces did not present any evidence of prezygotic and postzygotic incompatibilities, suggesting that both populations collected from soybean plants belonged to a single wide-ranging species. Prezygotic and postzygotic incompatibilities were detected between populations collected from different crops (soybean and bean). These incompatibilities may be caused by the different nutrients that each plant species renders, or the specific pest control strategies which may affect C. includens behavior. Studies of the genetic structure of C. includens populations based on mating isolation on other crops, as well as of the impact of management strategies on the specie, will increase understanding of the reproductive compatibility revealed by the present study.